Publisher Correction: Spatio-temporal expression of ANK2 promotes cytokinesis in oocytes - Tetkova, Anna; Jansova, Denisa; Susor, Andrej (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.